Development of a two-dimensional piezoelectric traveling-wave generator. (June 2021) - Lin, Yu-Min; Hsu, Yu-Hsiang; Su, Wen-Chun; Kao, Yuan-Ting; Lee, Chih-Kung
In this article, we present a new method to control the direction of traveling waves in either an x -direction or y -direction on a two-dimensional square plate. The core structure was composed of a piezoelectric serial bimorph with four electrodes. Each electrode was spatially designed to activate one of the bending modes and which included the ability to reduce adjacent modes and minimize interference. Our new method differs from other reported methods in that the four electrodes were driven at designated resonant frequencies. In our wave generator, different driving amplitudes and phases were applied to induce the traveling waves to propagate in a specific direction. To design the directional movement and to better understand the pattern of induced traveling waves, an analytical solution was derived to assist in the design of the four driving electrodes. Using our newly developed analytical method, traveling waves can be controlled to travel in either the x -direction or y -direction using two different sets of electrodes, where each electrode can be driven at a specific but different bending mode. We found that both the voltage ratio and phase difference between the two driving electrodes are important factors for optimization.